2015
DOI: 10.1016/j.jembe.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Intra-specific responses of Cymodocea nodosa to macro-nutrient, irradiance and copper exposure

Abstract: Excess macro-nutrients, metal contamination and light limitation are three of the most commonly encountered anthropogenic stressors affecting seagrass meadows. In this study, the effects of different combinations of nutrients (N-NO 3 , P-PO 4 ), copper and irradiance were investigated in shoots of Cymodocea nodosa collected from three meadows in the N. Aegean Sea, one (Nea Karvali) impacted by anthropogenically-derived environmental stressors and two in more pristine condition (Thasos, Brasidas). In a series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 70 publications
(84 reference statements)
0
8
0
5
Order By: Relevance
“…The potential of heavy metal accumulation in seagrass has been investigated for bioremediation purposes (e.g., Bunluesin et al, 2007;Govers et al, 2014). Although some of elements are essential to plant growth (e.g., Cu, Fe, Mn, Ni, and Zn), several studies have shown that heavy metals negatively impact seagrass photosynthetic physiology (Prange and Dennison, 2000;Macinnis-Ng and Ralph, 2002;Papathanasiou et al, 2015). For instance, Prange and Dennison (2000) found that two Halophila species were affected by exposure to Fe and Cu, whereas Zostera capricorni was only impacted by Cu.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of heavy metal accumulation in seagrass has been investigated for bioremediation purposes (e.g., Bunluesin et al, 2007;Govers et al, 2014). Although some of elements are essential to plant growth (e.g., Cu, Fe, Mn, Ni, and Zn), several studies have shown that heavy metals negatively impact seagrass photosynthetic physiology (Prange and Dennison, 2000;Macinnis-Ng and Ralph, 2002;Papathanasiou et al, 2015). For instance, Prange and Dennison (2000) found that two Halophila species were affected by exposure to Fe and Cu, whereas Zostera capricorni was only impacted by Cu.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, lamun juga mempunyai ciri-ciri sebagai berikut yaitu tidak ada stomata, mempunyai kutikula yang tipis, perkembangan schizogenous dari sistem lakunar, pollinasi yang hidrofil, dan tidak ada diafragma pada sistem lakunar (Goltenboth et al 2012). Distribusi dan stabilitas komunitas lamun ditentukan oleh faktor-faktor antara lain: nutrien, cahaya, sedimen, salinitas, dan suhu (Papathanasiou et al 2015;Kilminster et al 2014;Koch et al 2007;Moreno et al 2014;Kaldy et al 2015).…”
Section: Pendahuluanunclassified
“…Pada sedimen karbonat (mineral sedimen berasal dari terumbu karang), fosfat berinteraksi dengan karbonat dan kurang tersedia sebagai fosfat bebas. Di padang lamun, hal tersebut mungkin menyebabkan fosfor terbatas (Kilminster et al 2014;Papathanasiou et al 2015). Tetapi hal ini masih terbantu oleh kelebihan lamun yang dapat mengambil zat hara seperti amonia dan fosfat melalui daun walaupun konsentrasi hara pada kolom air pada umumnya sangat rendah.…”
Section: Metodeunclassified
See 2 more Smart Citations